Pilgrim’s Progress: Creating Growth in School for Young People Following Adversity. The Experience of Pupils in a Specialist Setting. - Lee, Beverley (2017)
This study examines the lived experience of pupils within a specialist school setting in order to help improve our understanding of post-traumatic growth. The sample comprises six pupils at The Pilgrim School in Lincolnshire (a hospital school), all of whom were exposed to traumatic events and subsequent mental health diagnosis prior to their time at the school. Participants were interviewed and data analysed using Interpretative Phenomenological Analysis. Results are congruent with existing literature. Two superordinate themes were identified as facilitators of growth: internal traits and external factors. Internal traits comprised of mastery, autonomy and a sense of belonging and external factors of a supportive emotional environment, positive relationships and a supportive physical environment. The two main themes can influence each other and are presented as an evolving cycle whilst the complex relationship between individual sub-components is demonstrated as a honeycomb effect. Whilst all appear to facilitate growth individually it is suggested that they are most effective as a whole. The study concludes by linking analytical observations with existing post-traumatic growth theory, offering valuable insight from the perspective of young people. Implications to the fields of trauma care for young people and the education sector are considered alongside areas for possible extended research.